Separated at Birth: The Politics of Pharmacare for All in Canada and Medicare for All in the United States; Comment on "Universal Pharmacare in Canada" - Carolyn Hughes Tuohy (Kerman University of Medical Sciences, 2021)
Policy decisions about healthcare coverage in Canada and the United States in the 1960s placed two virtually identical systems on different evolutionary paths in the physician and hospital sectors. However, prescription drug coverage remained outside Canada's single-payer model, and employer-based coverage continued to be the norm for the workforce population, as is the case across the broad healthcare system in the United States. As a result the current debate about pharmacare in Canada mirrors in political microcosm the larger debate on universal health insurance among American Democrats. In each case the near-term prospects for a single-payer plan appear slim.